Clinical and dosimetric feasibility of sparing submandibular gland in patients with oral cavity squamous cell carcinoma - Yi-Peng He; Ping Zhou; Li-Mei Guan; San-Gang Wu (Annals of Medicine)
Background To investigate the incidence of submandibular gland (SMG) involvement and explore the feasibility of sparing SMG in the oral cavity squamous cell carcinoma (OSCC).Methods This study retrospectively analyzed patients between January 2018 to October 2022. Ten patients with tongue squamous cell carcinoma receiving postoperative radiotherapy were replanned to investigate the feasibility of sparing SMG. The dose constraint for the SMG was a mean dose (Dmean) <39 grey (Gy).Results A total of 238 patients were identified and 105 had metastatic neck lymph nodes. Level II was the most common site of metastasis (n = 94, 89.5%), followed by level IB (n = 37, 35.2%), level III (n = 26, 24.8%), level IA (n = 3, 2.6%), and level IV (n = 2, 1.9%). A total of 50 metastatic lymph nodes were located at the level IB, of which 18 (36.0%), 29 (58.0%), and 3 (6%) were located in the lateral, anterior, and inferior aspect of the SMG. No metastatic lymph nodes were found within or on the medial aspect of the SMG. The Dmean of the SMG was <39 Gy in all patients with a Dmean of 38.8 Gy. The median dose of PTV54 D95% was 53.8 Gy, which met the prespecified allowable coverage goal.Conclusions Our study suggests that SMG involvement is rare in OSCC. With strict imaging and clinical evaluation, sparing SMG during radiotherapy is feasible.